A few dark shadows in the information society - D'Alí²s-Moner, Adela (Anuario ThinkEPI, 2013)
We speak about the "information society", but very often without any critical consideration. This article considers whether we can really say that we live in the "information society" and raises questions regarding the information that we receive from big business, political powers and stakeholders, inequalities between countries and social classes, and other topics such as net neutrality or social networks.
Keywords: Information society; Disinformation society; Digital divide; Net neutrality.